PENGUATAN PENDIDIKAN KARAKTER DISIPLIN PADA SISWA SEKOLAH DASAR - Anita Rachman Ainur Rofiqoh; Hanifah Dillah; Rossabela Rindiyanto (PROCEEDING UMSURABAYA, 2022)
The problem that is often felt by educators is the decline in character values in children, especially the character of discipline. The occurrence of undisciplined behavior in schools shows that there are serious problems in discipline and morality education. The emergence of undisciplined behavior indicates that the knowledge related to character acquired by students at school does not have a positive effect on changes in students' daily behavior. Therefore, the teacher's role in learning must really master the concept of evaluating attitudes, both spiritual and social attitudes that lead to the learning process. This type of research uses descriptive research with a qualitative approach. This study aims to provide an overview of the incident, for example planting discipline characters in children. In this study, students were used as research subjects. in data collection techniques researchers use more observations and interviews. Based on interviews with 6th grade teachers of SD Muhammadiyah 11 Surabaya, information can be obtained that there are still many elementary school students, especially high class students who still do not apply discipline in daily life. There are so many factors that make disciplined behavior difficult to change, such as factors from the family, habits in everyday life, and many factors that can influence the student's habits. Therefore, there is a need for direct examples from educators that need to be implemented in everyday life so that disciplinary behavior can be effectively applied by students. Discipline is easy to develop by studying Pancasila education. This can be seen from several indicators, such as: students no longer cheat in written exams, students come on time, students do homework seriously, and do not plagiarize friends' homework. Furthermore, student discipline is formed because of the teacher's example, his example, making every behavior an example for students.Â Keywords: Character Education, Discipline